Preclinical delayed toxicity studies of BCMA CAR T-cell injection in B-NDG mice with multiple myeloma - Guo, Jianmin; Wu, Qiqi; Li, Hongjian; Liang, Chun; Dai, Jinlong; Zhang, Shuren; Dai, Cailing; Zhang, Jishuai; Wen, Yuying; Yang, Wei (Frontiers in Immunology, 2024)
Based on the efficacy data from the previous study of BCMA CAR-T cells, we further investigated the delayed toxicity for 8 weeks after a single dose of BCMA CAR-T cell injections to observe possible toxic reactions. B-NDG mice transplanted with multiple myeloma cancer were given one dose of low and high-dose BCMA CAR-T cells. Examination includes clinical signs, weight and food intake, clinicopathology, cytokine, T-lymphocyte subpopulation, and histopathology. Biodistribution of CAR DNA fragments was quantified by qPCR. The results showed no mortality or significant toxic effects were observed in CAR-T cell-treated groups. Compared to model group, restorative changes in clinical signs and clinicopathology indicate therapeutic effects in the CAR-T cell-treated groups. Human-derived cytokines IFN-γ levels showed a geometric increase due to the GVHD response induced in the mice. pathology results indicated that BCMA CAR-T cell treatment groups showed mixed cellular infiltration of human-derived T cells, cancer cells in several organs including the liver, spleen, lung and kidney, but showed mild damage compared with the severity damage in same dosage of human normal T cells as well as the model group. The distribution of BCMA CAR-T cells was highly consistent with that of MM cells, suggesting that BCMA CAR-T cells could follow the cancer cells during metastatic targeting of the tissues. The present study demonstrated low BCMA CAR-T cell injection toxicity, with manageable side effects and good anticancer activity and without observable adverse effects. This study provides data to support future clinical studies of BCMA CAR-T cell injection for MM.